A Case Study on Stabilizing Kathmandu Valley Lacustrine Silt with Stone Dust and Sand - Niraula, Ujjwal; Dahal, Bhim Kumar (Everest Advances in Science and Technology, 2025)
High-plasticity soils, like those in the Kathmandu Valley, present significant construction challenges because of their high compressibility, low shear strength, and notable settlement behavior. By evaluating changes in geotechnical properties and shear strength parameters, this study explores the stabilization potential of stone dust and sand in enhancing the geotechnical behavior of lacustrine silt, a common high-plasticity soil type in the Kathmandu Valley. A number of laboratory tests were performed on natural soil samples that were collected from the area close to the Bagmati River. Different proportions of stone dust (10–40%), sand (10–40%), and a combination of the two were used to modify the soil. Assessments were made of parameters like cohesion, internal friction angle, maximum dry density (MDD), and optimal moisture content (OMC). Sand and stone dust increased the internal friction angle and dry density while decreasing cohesion and OMC. It was discovered that the combination of sand and stone dust was especially useful for strength improvement without being overly expensive. According to the study, sand and stone dust are both practical, locally accessible stabilizers that can greatly increase the bearing capacity and lessen the settlement of high-plasticity soils, particularly for shallow foundations used in low-rise buildings.